Interaksi Guru dan Siswa dalam Pembelajaran IPS di Sekolah Dasar - Anisa Maharani Azzahra; Husnul Chotimah; Aulia Dewi Rachmawati; Muhammad Naufal Zaidan; Uswatun Hasanah; Fadila Romadona Izzati; Maria Fasela Nurdianto; Erni Erni; Muhammad Kaulan Karima (Journal Innovation In Education, 2025)
This research aims to describe the form of interaction between teachers and students in Social Sciences (IPS) learning in elementary schools and identify factors that support and hinder this interaction. The approach used is descriptive qualitative with data collection through observation, interviews and documentation at UPTD SD Negeri 6 Metro Utara. The research results show that teachers use various methods such as lectures, discussions, Problem Based Learning (PBL), and educational games to build effective and enjoyable interactions. Teachers also play an important role in creating a positive learning atmosphere through a cheerful attitude and friendly approach. Student responses show that discussion and game methods can increase their motivation and participation. However, there are obstacles such as differences in learning styles and student characters, especially for shy students who feel less comfortable in open discussions. Therefore, inclusive and adaptive strategies are needed so that all students can be actively involved. Support from the school is also an important factor in forming conducive interactions. The success of interaction in social studies learning is influenced by appropriate teaching methods, teacher attitudes, student character, and a supportive learning environment.